OHVIRA: Uterus didelphys, blind hemivagina and ipsilateral renal agenesis: Advantage MRI - Sunil K Bajaj; Ritu Misra; Brij B Thukral; Rohini Gupta (Wolters Kluwer Medknow Publications, 2012)
We present here a case of an uncommon complex uterine anomaly - Obstructed HemiVagina with Ipsilateral Renal Agenesis (OHVIRA), also known as Herlyn-Werner-Wunderlich syndrome in a 14-year-old girl along with sonographic (trans-abdominal and trans labial), and MRI findings. The patient underwent surgery wherein imaging findings were confirmed. An MRI has proved to be of great help in correct diagnosis avoiding surgical interventions/ laparoscopy, which were needed in past to diagnose this rare anomaly. We also discuss the development of this anomaly with the help of a relatively new theory of uro-genital development by Acien and review the literature.